Climate variability of the East Asian winter monsoon and associated extratropical–tropical interaction: a review. Issue 1 (14th June 2021) - Ma, Tianjiao; Chen, Wen
Abstract: The East Asian winter monsoon (EAWM) is one of the most important climate systems during boreal winter. It has a large meridional extent and provides a vital bridge between the mid‐to‐high latitudes and the tropics. This paper reviews the latest research on the climate variability of the EAWM, with particular emphasis on the associated processes of extratropical–tropical interaction. Some new results have been achieved in understanding the variation of the EAWM on interdecadal, interannual, and intraseasonal time scales, such as the interdecadal strengthening in the early 21st century, the unstable impact of El Niño–South Oscillation (ENSO) on the EAWM, and the intraseasonal strong cold events in East Asia. In addition, understanding of the extratropical–tropical interactions related to the EAWM has improved in several aspects, including the impacts of the EAWM on ENSO‐related climate effects, and the variation of regional Hadley circulation over the western Pacific and its climate impacts in the Asia–Australia region. Moreover, recent work has systematically evaluated the capacity of climate models to simulate the EAWM, including its climatology, interannual to interdecadal variations, and its relationship with ENSO. Finally, some scientific issues regarding our understanding of the EAWM are proposed for future investigation. Abstract : The East Asian winter monsoon (EAWM) is one of the most important climate systems during boreal winter. It has a large meridional extent and provides a vital bridge between the mid‐to‐high latitudes and the tropics. This paper reviews the latest research on the climate variability of the EAWM, with particular emphasis on the associated processes of extratropical–tropical interaction.